Crystal structures, selective fluorescent sensing and photocatalytic properties of cobalt(II) and copper(II) coordination architectures with 2, 4, 5-tri(4-pyridyl)-imidazole. Issue 23 (2nd December 2018) - Wang, Jun-Jie; Cao, Ya-Li; Li, Xiao-Ru; Wang, Yi-Ran; Li, Yan-Ang; Tian, Lu-Lu; Hu, Tong-Liang
Abstract: Solvothermal reaction of M II (M = Co, Cu) ions with 2, 4, 5-tri(4-pyridyl)-imidazole (Htpim) gave two MOFs, [Co1.5 (tpim)(FA)2 (H2 O)] n (1 ) and [Cu2 (Htpim)(tpim)(FA)(NO3 )2 (DMF)] n (2 ) (HFA = formic acid, DMF = N, N-dimethylformamide). Single-crystal X-ray diffraction analyses indicated that 1 exhibits a 3D {4 3 .4 12 } topology framework assembled by hexanuclear [Co6 (FA)8 (H2 O)4 ] units and tpim ligands, while 2 presents a 2-D double layer {4.6 2 }2 {4 2 .6 4 .8 2 .10 2 }{6 2 .8} network. Hereinto, an inorganic acid was not only used to adjust the pH value of reaction system but also to act as an oxidizing agent to participate in in situ organic reactions. Moreover, 1 displays high sensitivity in the detection of nitrobenzene as a fluorescent sensor and exhibits a relatively good photocatalytic activity toward the degradation of rhodamine B in aqueous solution under UV irradiation. Graphical Abstract: